POTENTIAL USE OF DIFFERENT FERTILIZERS ON THE GROWTH OF Brachionus sp. - Shefia Marchelin; Yuli Andriani; Zahidah Hasan; Ujang Subhan (Universitas Mataram, 2024)
Brachionus sp. is a zooplankton that is widely used by farmers as natural feed for fish larvae stages. In the process of cultivating Brachionus sp. it is necessary to fulfill the nutritional needs for its growth by providing fertilizer. The use of natural fertilizer as a culture medium for Brachionus sp. using fertilizers such as chicken manure, Urea, NPK, TSP, and POC. This study aims to determine the potential use of different fertilizers in the growth of Brachionus sp. The method used is a literature study. The results obtained from the potential use of different fertilizers in the culture of Brachionus sp. namely the concentration of 300 mg of chicken manure; 7.5 mg TSP; 6 mg Urea; 0.45 gr of Bread Yeast per 3 L of water enriched with 0.30 gr Extrajoss produced the highest population density of 5.01 ind/mL. In addition, the concentration of chicken manure fertilizer between broiler chickens and kampung chickens was 2 L of water; 4 mg urea; 3 mg TSP; 400 mg of broiler chicken manure produced the highest productivity of 89,639 ind/2 L.